Patterns of elephant utilization of Borassus aethiopum Mart. and its stand structure in the Pendjari National Park, Benin, West Africa - SALAKO, Kolawolé Valère; HOUEHANOU, Thierry; Yessoufou, Kowiyou; ASSOGBADJO, ACHILLE EPHREM; AKOEGNINOU, AKPOVI; Glèlè kakaï, Romain (My University, 2017)
Understanding interactions of elephants with threatened plant species is crucial to guide conservation decisions in protected areas (PAs). This study focused on the dioecious palm Borassus aethiopum Mart. in the Pendjari National Park (PNP). The aim was to assess elephant damages to the palm, and compare the stand structure (adult sex-ratio, density, height, diameter, and survival of regenerations) of the palm in stands of high versus low elephant pressure (EP). Data were collected in 60 square-plots of 0.25 ha each in five stands of B. aethiopum. Analysis of variance and generalized linear models were used for statistical analyses. Adult uprooting (57.80 ± 3.32%) and sapling grazing (79.87 ± 1.02%) were the most commonly occurring damage. High EP significantly (ANOVAs, P < 0.05) reduced adult densities (from 107.60 ± 4.50 individuals ha-1 to 33.50 ± 1.73 individuals ha-1). However, high EP promoted seedling transition to sapling (from 0.10 ± 0.02 to 0.20 ± 0.02), but prevent transition of sapling to juvenile (from 0.12 ± 0.03 to 0.01 ± 0.00). For the adult sex-ratio, no significant variation (Nested GLM with binomial error, P = 0.82) between EPs and no significant departure from 50:50 (Exact binomial tests, P > 0.05) were observed, suggesting that adult uprooting is not sex-specific. We conclude that high EP limits functional diversity of the B. aethiopum in savannah ecosystems, and may cause decline of the palm species. Management actions should improve the survival of sapling palms by the use of barbed wire to protect several patches of saplings from EP. In addition, because the PNP belongs to a regional network of PAs, a regional management plan of elephant populations would yields better outcome.
Keywords: Borassus aethiopum; herbivory; Loxodonta africana; stand structure